(untitled) - Rogers, Lisa Waller; 1955- (Lubbock, Texas, 2001)
A teenage boy keeps a diary of events during the devastating hurricane which struck Galveston, Texas, in 1900, and of the rescue operations that followed.
Accelerated Reader AR
Keywords: Hurricanes; Fiction; Texas